The Kinetics of Joined Action of Triplet-Triplet Annihilation and First-Order Decay of Molecules in T1 State in the Case of Nondominant First-Order Process: The Kinetic Model in the Case of Spatially Periodic Excitation - Paweł Borowicz; Bernhard Nickel (Journal of Spectroscopy)
In this paper the model developed for estimation of the diffusion coefficient of the molecules in the triplet state is presented. The model is based on the intuitive modification of the Smoluchowski equation for the time-dependent rate parameter. Since the sample is irradiated with the spatially periodic pattern nonexponential effects can be expected in the areas of the constructive interference of the exciting laser beams. This nonexponential effects introduce changes in the observed kinetics of the diffusion-controlled triplet-triplet annihilation. Due to irradiation with so-called long excitation pulse these non-exponential effects are very weak, so they can be described with introducing very simple correction to the kinetic model described in the first paper of this series. The values of diffusion coefficient of anthracene are used to calculate the annihilation radius from the data for spatially homogeneous excitation.